(untitled) (2015)
In the 90's, the Colombian politics showed an institutional and party crisis as a consequence of the corruption, the armed conflict, the lack of legitimation of the State institutions and the standstill of the traditional political parties. This situation forced both the political candidates and the parties, to use professional techniques and strategies commonly used in the United States to attract electors. In this study, we intend to empirically demonstrate the level of professionalization of the presidential campaign of 2010 in Colombia, which is important in the political scene because it comes after an eight years period of government, due to the re-election of the President with the highest popularity in the history of the country. Moreover, at that time tool place the consolidation of political parties and movements, without ideological links: U Party and Green Party.